Landrace maize treated with bioinputs and natural phosphate tolerates water deficit (Research, Society and Development, 2025)
This study aimed to evaluate whether reactive natural phosphate (RNP), combined with plant growth-promoting microorganisms (PGPM), promotes the growth of creole maize (Zea mays L.) plants cultivated under water déficit (WD) conditions. The experiments were conducted in a greenhouse and followed a completely randomized design, with combinations of WD, RNP, and microorganisms (Azospirillum – Az; Bacillus subtilis + Bacillus megaterium – BsBm; and efficient microorganisms – EM). The following variables were determined: shoot height (SH), stem diameter, number of leaves (NL), chlorophyll content and fluorescence (Fv/Fm), internal CO₂ concentration (Ci), water use efficiency (WUE), transpiration rate (E), stomatal conductance (gs), and net photosynthetic rate (A). An increase in SH was observed under WD and in the average (with and without WD) of treatments with RNP combined with Az, BsBm, or EM. Under WD, leaf Ci decreased by 22% and 12% in the control and Az treatments, respectively. Conversely, Ci increased 1.4 times with EM, BsBm, RNP+Az, and RNP+BsBm under WD. The highest WUE values were found in the RNP+BsBm and RNP+EM treatments (8% and 12%, respectively). WD increased WUE in the control and Az treatments. Under WD, A/Ci increased up to 34% in the control and Az treatments, while BsBm and RNP+Az led to a 30% reduction. Therefore, bioinputs promoted maize growth under both water availability conditions. A 50% reduction in water supply did not alter physiological parameters, indicating stress tolerance in the evaluated landrace genotype.